2021
DOI: 10.1111/jfpp.15587
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lemon albedo as fat replacer for development of ultra‐low‐fat chicken patties

Abstract: The study was carried out to develop ultra-low-fat chicken patties with incorporation of lemon albedo powder. Chicken patties were developed by incorporating lemon albedo powder as fat replacer at 1.0%, 2.05, 3.0% level to replace 50% vegetable oil in formulation. Emulsion and product pH, emulsion stability, fat and cholesterol decreased significantly (p < .05), however cooking yield, moisture content, fat retention and moisture retention values increased significantly (p < .05) in treatments. All mineral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
6
7
0
Order By: Relevance
“…Also, the increase in pH during frozen storage is due to the breakdown of protein, mainly amines. Similar findings were obtained by Chappalwar et al [ 58 ]. They found that the addition of lemon peel powder to the chicken patties led to a decrease in the pH values, which may be attributed to the presence of polyphenols and flavonoids in lemon albedo as hesperidin, eriocitrin, and naringin.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Also, the increase in pH during frozen storage is due to the breakdown of protein, mainly amines. Similar findings were obtained by Chappalwar et al [ 58 ]. They found that the addition of lemon peel powder to the chicken patties led to a decrease in the pH values, which may be attributed to the presence of polyphenols and flavonoids in lemon albedo as hesperidin, eriocitrin, and naringin.…”
Section: Resultssupporting
confidence: 92%
“…In general, gumminess values were increased slightly with increasing the frozen storage time. Similar results were obtained by Chappalwar et al [ 58 ] who observed a decrease in hardness, gumminess, cohesiveness, and springiness values of chicken patties by increasing the ratio of lemon albedo powder. They attributed this to the effect of lemon albedo on the protein system, the presence of water, and the binding of fats in the lemon peel which provides a smooth texture.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations